Science Interval Project: We Can Teach and Learn Physics During the Leisure - de Araújo, Francisco Adeil Gomes; de Oliveira, Meirivâni Meneses; Nobre, Eloneid Felipe (Scientia in educatione, 2017)
The break between classes, still seen as an unproductive interval of time, in recent years, has been a cause of worry to the school community. The Science Interval Project aims to combine the science education with leisure time during the interval school, attracting the students for a time of learning and discovery. Speciﬁcally, the project aims to provoke and inspire the student to discover, build and give new meaning to knowledge and present to the school community the work developed in the classroom by the teacher and his students.